Fostering Disciplinary Literacy: Mathematics Teaching Strategies in Early Childhood Education - Farhatul Kamillah (SEAMEO CECCEP, 2025)
Abstract— Fostering disciplinary literacy skills from an early age is essential to prepare young children for educational success in the future. This study explores teaching strategies to develop disciplinary literacy, particularly in mathematics within early childhood education (ECE). Drawing on a literature review approach, this paper integrates three key frameworks: the Developmentally Appropriate Practice (DAP) by the National Association for the Education of Young Children (NAEYC), the 4Es heuristic model by Moje (2015), and the eight mathematical practices outlined in the Common Core State Standards (CCSS). The findings highlight three main strategies that considered effective in promoting disciplinary literacy in mathematics: (1) involving children with their social rich learning environment; (2) implementing play-based learning to foster cognitive, linguistic, and social development; and (3) facilitating conversation-rich instruction to encourage problem solving and mathematical reasoning. These strategies are essential in scaffolding children’s abilities to read, write, and comprehend mathematical concepts within disciplinary contexts. Additionally, introducing these practices in early education contributes to build a strong academic foundation for children and promotes critical engagement with disciplinary knowledge in later years.